Salmonellatyphimurium in the Australian egg industry: Multidisciplinary approach to addressing the public health challenge and future directions. Issue 12 (13th August 2017) - Chousalkar, Kapil K.; Sexton, Margaret; McWhorter, Andrea; Hewson, Kylie; Martin, Glen; Shadbolt, Craig; Goldsmith, Paul
ABSTRACT: In Australia, numerous egg-related human Salmonella typhimurium outbreaks have prompted significant interest among public health authorities and the egg industry to jointly address this human health concern. Nationwide workshops on Salmonella and eggs were conducted in Australia for egg producers and regulatory authorities. State and national regulators represented Primary Production, Communicable Disease Control, Public Health and Food Safety, and Food Standards Australia and New Zealand. All attendees participated in discussions aimed at evaluating current evidence-based information, issues related to quality of egg production, and how to ensure safe eggs in the supply chain, identifying research gaps and practical recommendations. The perceptions from egg producers and regulatory authorities from various states were recorded during the workshops. We presented the issues discussed during the workshops, including Salmonella in the farm environment, Salmonella penetration across eggshell, virulence in humans, food/egg handling in the supply chain, and intervention strategies. We also discussed the perceptions from egg producers and regulators. Recommendations placed emphasis on the future research needs, communication between industry and regulatory authorities, and education of food handlers. Communication between regulators and industry is pivotal to control egg-borne S. typhimurium outbreaks, and collaborative efforts are required to design effective and appropriate control strategies.